다한증의 제한적 교감신경절단술 - 박만실; 서충헌; 심재천; 최봉춘; 이영철 (Taehan Hyungbu Oekwa Hakhoe chi, 1999)
Background: Conventional thoracoscopic thoracic sympathectomy or sympathicotomy is an effective method in treating localized hyperhidrosis; however, this may result in a postoperatively embarrassing compensatory hyperhidrosis or facial anhidrosis in the treatment of palmar hyperhidrosis. We modified the conventional sympathicotomy by limiting the extent of nerve transection. The purpose of this study was to assess the result of the limited thoracoscopic sympathetic nerve transection in hyperhidrosis. Material and Method: From May to August 1998, 17 patients underwent limited transection of the sympathetic nerve. For 9 patients with facial hyperhidrosis, we transected only the interganglionic fiber between the first and the second ganglion, whereas the conventional method cuts two interganglionic fibers. Eight patients with palmar hyperhidrosis underwent limited transection of the interganglionic fiber between the second and third ganglion. Result: Sixteen patients had improved symptom postoperatively. There was a recurred facial sweating in 1 patient 1 month after the operation. Among the 9 facial hyperhidrosis patients, postoperative compensatory hyperhidrosis was severe in 4, moderate in 4 and minimal in 1. But in 8 cases of palmar hyperhidrosis compensatory hyperhidrosis was moderate in 3, and minimal in 1, none in 4. Facial sweating was not disturbed postoperatively in all of the palmar hyperhidrosis patients. Conclusion: Limited sympathetic nerve transection is a practical and less invasive method for the treatment of localized hyperhidrosis and may reduce the incidence of compensatory truncal hyperhidrosis and facial anhidrosis in case of palmar hyperhidrosis. 배경: 국소적 다한증의 흉강경을 이용한 통상적인 흉부교감신경절제술이나 교감신경절차단술은 효과적인 치료법이기는 하나 수술 후 심한 보상성 다한증이 많이 발생 하고 수장부 다한증의 경우 수술 후 얼굴에서 땀이 나지 않는 부작용이 발생한다. 저자들은 기존의 수술법을 개량해 제한적 흉부교감신경절단술을 고안하였다. 본 연구는 제한적 교감신경절단술의 결과를 분석하였다. 대상 및 방법: 1998년 5월부터 8월 까지 17명의 환자들에게 제한적 흉부교감신경절단술을 시행하였다. 9명의 안면부 다한증인 환자들에게 두 번째 교감신경절 위 아래의 교감신경을 절단하던 기존의 방법과는 달리 첫번째 와 두 번째 흉부교감신경절 사이의 신경절간신경만을 절단하였다. 8명의 수장부 다한증 환자에 대해서는 두 번째와 세 번째 흉부 교감신경절간신경을 절단하였다. 결과: 17명의 환자들 중 16명의 환자에서 수술 후 원하던 부위의 땀이 나지 않았으나 1명의 환자는 수술 1달 후 얼굴의 땀이 재발하였다. 안면부 다한증으로 수술을 받았던 9명의 환자들 보상성 다한증으로 4명이 심하게, 4명이 중등도로, 1명은 경미하게 불편을 호소 하였다. 그러나 수장부 다한증으로 수술을 받았던 8명의 환자들 중에서는 보상성 다한증을 3명에서 중등도로, 1명이 경미하게 호소하였으며 4명은 보상성 다한증이 없었다. 결론: 제한적 흉부교감신경절단술은 최소 침투 수술법으로 효과적인 치료법이며 특히 수장부 다한증에서는 수술 후 체간에서 발생하는 보상성 다한증의 발생을 줄이고 얼굴의 무한증을 막을 수 있을 것으로 사료된다.